Redescription of the South American genus Caleucoela and description of the male of C. striatipennis (Hymenoptera: Figitidae: Eucoilinae: Ganaspini) - Vanina Anadina Reche; Fabiana Gallardo (Caldasia)
The South American genus Caleucoela Kieffer, 1909 is redescribed and its geographic distribution is updated. Its only species, Caleucoela striatipennis Kieffer, 1909 is redescribed, including the first de-scription of the male and a new record from Peru.